Pelatihan Komputer Dasar Bagi Kader PKK dan Posyandu Di Desa Patikraja - Linda Perdana Wanti; Eka Tripustikasari (Madani : Indonesian Journal of Civil Society, 2019)
Empowerment of Family Welfare or often abbreviated as PKK is a movement that has been built from the center to the village and its existence and benefits have been felt by the community. This PKK activity is reflected in the 10 PKK Principal Programs, one of which is focused on health and attention specifically aimed at maternal and child health. So that an Integrated Service Post (Posyandu) was formed consisting of trained Posyandu cadres. These trained Posyandu cadres are not only seen from the way they handle maternal and child health but also must be supported by their ability to use computers in the process of recording and data collection. However, not all PKK and Posyandu Cadres, especially in villages, are adept at using computers, for example, PKK Cadres and Patikraja Village Posyandu. In fact, many cadres are new to computers and cannot use standard programs such as Microsoft PowerPoint and Microsoft Word. The goal of this community service program is to improve the capabilities and competencies of PKK Cadres and Patikraja Village Posyandu in operating computers to support good and smooth performance in terms of administration and data collection. Based on the results of the evaluation it was seen that PKK cadres and the Patikraja Village Posyandu attended the training with great enthusiasm and they were able to practice the material very well.